The Many Scales in the Universe JENAM 2004 Astrophysics Reviews - Toro Iniesta, J.C; Javier Alfaro, Emilio; Gorgas, Javier Garcia; Salvador-Solé, E.; Butcher, H. (Springer Netherlands : Imprint: Springer, 2006)
The book gathers the invited talks to the XIII JENAM conference, organized this time by the European Astronomical Society (EAS) and the Spanish Astronomical Society (SEA), and hosted by the Instituto de Astrofísica de Andalucía (CSIC). All branches of astrophysics are encompassed from the largest scales and cosmology to the solar system and the Sun, through the galaxies and the stars, including a section on astronomical instrumentation. Very relevant experts from all over the world speak in a single book about the most recent, exciting results from their fields in a way which is useful for both researchers in these fields and colleagues working in other disciplines. The book is accompanied by a CD-ROM including the remaining contributions of the meeting in PDF format, hence opening a wide panorama of what is going on in astrophysics nowadays.